1991
DOI: 10.1017/s0003356100020158
|View full text |Cite
|
Sign up to set email alerts
|

The digestion and utilization of amino acids of heat-treated fish meal by growing/finishing pigs

Abstract: A batch offish meal was (a) untreated, (b) heated to 130°C and (c) heated to 160°C under controlled conditions.In trial 1, these materials were incorporated into a diet based on barley meal (278·7 g/kg), wheat starch (412·5 g/kg), maize meal (245·3 g/kg) and tallow (33·5 g/kg) at a rate of inclusion of 100 g/kg. Diets contained a vitamin/mineral pre-mix together with the inert marker titanium dioxide and were given to four pigs fitted with simple T-piece Heal cannulas over four time periods each of which laste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
1
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 16 publications
6
19
1
1
Order By: Relevance
“…The apparent ileal digestibilities of AA in this study (Table 2) are in the range of values for growing pigs fed diets containing fish meal as the sole source of protein (Knabe et al 1989;Wiseman et al 1991). This suggests that the protein in fish meal is easily digested by weanling pigs.…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…The apparent ileal digestibilities of AA in this study (Table 2) are in the range of values for growing pigs fed diets containing fish meal as the sole source of protein (Knabe et al 1989;Wiseman et al 1991). This suggests that the protein in fish meal is easily digested by weanling pigs.…”
Section: Resultssupporting
confidence: 51%
“…Improvements in protein digestibility can be achieved if fish meal is heated at 70oC under vacuum instead of just being heated at 100oC (Danielsen et al 1991). Excessive heat treatment (160oC) reduces (P < 0.05) the apparent ileal digestibilities of AA in fish meal (Wiseman et al 1991). The fish meals used by Jgrgensen et al (1984) may have originated from a different fish species or contained more bone than the fish meal used in this study.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…La humedad fue de 6.89 ± 0.41, y está acorde con los parámetros internacionales, la humedad ideal de la harina al final del proceso, no debe sobrepasar el 10% de agua, ni debe bajar del 6%; si es inferior, significa que se ha recalentado, y su calidad nutritiva y proteica se ha alterado. Por el contrario, si está demasiado húmeda, no se puede vender y además puede desarrollar hongos y otras bacterias (Aguilera et al, 1974;Terrazas et al, 2005;Wiseman et al, 1991). La calidad del producto obtenido fue excelente, ya que el contenido de amoniaco libre (TVN) fue 14.38 ± 0.72 mg/100 g, valor inferior al máximo permisible (120 mg/100 g) en una harina estándar (Aguilera et al, 1974;Giannini, 2003;Terrazas et al, 2005).…”
Section: Resultados Y Discusiónunclassified
“…However, the failing of these assays is that they do not take into account the possibility that the digestion and absorption of unmodified lysine in a food protein may be less than 100 %. This is an important consideration since the amino acid (including reactive lysine) digestibility of processed foods or feedstuffs is often far from complete 29,32,48,64,89 . Moughan et al 46 using a heated glucose -casein mixture clearly demonstrated that considerable amounts of dietary reactive lysine were not absorbed from the small intestine of the growing pig ( Table 1).…”
Section: Determining Available Lysinementioning
confidence: 99%